1989
DOI: 10.1111/j.1651-2227.1989.tb11064.x
|View full text |Cite
|
Sign up to set email alerts
|

Allergic Diseases in Swedish School Children

Abstract: The occurrence of allergic diseases in children was studied on the basis of a questionnaire sent to the parents of 20,000 school children, 7, 10 and 14 years of age, in 3 parts of Sweden with different climatic conditions. The prevalence of asthma was 2.4%, allergic rhinoconjunctivitis 7.4%, eczema 7.8% and total allergic diseases 16.9%. The prevalence of all diseases was significantly higher in the northern part of the country than in the southern parts. This geographic variation was not related to heredity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
65
2
1

Year Published

1991
1991
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(77 citation statements)
references
References 23 publications
(2 reference statements)
9
65
2
1
Order By: Relevance
“…16 The presence of parental history of atopic symptoms doubled the incidence of atopic symptoms in the children if one of the parents was affected, and tripled the incidence if both parents were affected. 17 However, in our study, we found that maternal atopy was not associated with the incidence of atopic dermatitis.…”
Section: Discussioncontrasting
confidence: 73%
“…16 The presence of parental history of atopic symptoms doubled the incidence of atopic symptoms in the children if one of the parents was affected, and tripled the incidence if both parents were affected. 17 However, in our study, we found that maternal atopy was not associated with the incidence of atopic dermatitis.…”
Section: Discussioncontrasting
confidence: 73%
“…Our study for the first time provides an explanation why some studies of breast-feeding have observed a protective effect against asthma and atopy, 13,[22][23][24][25][26][27][28] whereas other studies showed an increased risk. [7][8][9][10][11][12] We are the first to analyze data from early childhood well into middle age.…”
Section: Discussionmentioning
confidence: 71%
“…Several studies 13,[22][23][24][25][26][27][28] and 2 recent meta-analyses 1,2 have reported a protective effect of breast-feeding in the first few years of life. We found exclusive breastfeeding did have a protective effect against risk of current asthma, infantile eczema, and food allergies at 7 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…An ecological analysis including 20 Brazilian centers presented a direct association between asthma prevalence and inappropriate sanitation conditions, child mortality, inequity index (GINI), and mortality of all causes 14 . Some studies, not only in Brazil but also in other Latin American countries, Europe, Asia, and Africa, found higher asthma (self-reported or symptoms) prevalence in the urban area when compared with the rural area [15][16][17][18][19][20][21] . The few studies carried out in the rural area suggest that population living there are protected from asthma or allergy for unknown reasons [22][23][24] .…”
Section: Discussionmentioning
confidence: 99%